African Diaspora Direct Investment Establishing the Economic and Socio-cultural Rationale (Palgrave Studies of Entrepreneurship in Africa,, 2018)
Examining the experiences of Africans setting up businesses back home, the main focus of this book is to establish the economic, social and psychological reasons for such 'home direct investment'. Despite the personal sacrifices that are often needed in order to set up new ventures, the diaspora invests relentless effort and motivations in the pursuit of home ventures. The authors explore critical areas such as the social and psychological pressures that African Diasporas experience when investing in their home countries, as well as the management of diaspora businesses and the impact of such investment to local economies.